Wczesnośredniowieczne cmentarzysko szkieletowe w Sowinkach (gm. Mosina, woj. poznańskie): analiza antropologiczna i paleodemograficzna - Kozak, Jerzy (Polskie Towarzystwo Antropologiczne, 1996)
This paper presents the results of anthropological examinations (morphological characteristics and paleodemographic analysis) of human bone remains (121 individuals) discovered in the cemetery at Sowinki (10th/11th century).
An early mediaeval cemetery at Sowinki (Mosina commune, Poznań voivodeship) - anthropological and paleodemographic analysis